1992
DOI: 10.1148/radiology.184.2.1620860
|View full text |Cite
|
Sign up to set email alerts
|

Reflex sympathetic dystrophy in the foot: clinical and scintigraphic criteria.

Abstract: To establish strict clinical criteria for reflex sympathetic dystrophy (RSD) of the foot and to characterize any associated scintigraphic pattern, the authors performed three-phase radionuclide bone scanning in 51 patients prospectively referred because RSD was a diagnostic consideration. To establish sensitivity and specificity data, the cases of an additional 100 consecutive patients referred for a variety of foot problems were retrospectively reviewed. The authors defined RSD of the foot as a pain syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(19 citation statements)
references
References 0 publications
0
15
0
4
Order By: Relevance
“…Les formes radiaires, unidigitales sont plus rares et d'expression plus difficile à reconnaître, facilement [5]. La scintigraphie osseuse aux biphosphonates marqués ( 99m Tc-MDP) est très sensible pour détecter des sites inflammatoires articulaire ou osseux mais manque de spécificité [6], limitée à 80 % lorsqu'il s'agit de différencier l'algodystrophie d'une autre cause inflammatoire [7].…”
Section: Discussionunclassified
“…Les formes radiaires, unidigitales sont plus rares et d'expression plus difficile à reconnaître, facilement [5]. La scintigraphie osseuse aux biphosphonates marqués ( 99m Tc-MDP) est très sensible pour détecter des sites inflammatoires articulaire ou osseux mais manque de spécificité [6], limitée à 80 % lorsqu'il s'agit de différencier l'algodystrophie d'une autre cause inflammatoire [7].…”
Section: Discussionunclassified
“…Any discrepancies were later resolved by consensus. Previously described scintigraphic criteria for RSD were used [10,12] . Typically, the TPBS demonstrated diffusely increased fl ow on the fl ow study, diffusely increased activity on the blood pool images and/or increased activity on the 3-hour delayed bone scan images with prominent juxta-articular uptake.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports have shown that TPBS has a sensitivity of up to 100% and a specifi city of up to 98% for the diagnosis of RSD [8][9][10][11][12] . For hemiplegics, a positive TPBS accurately predicts subsequent development of clinical symptoms of RSD [13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…als �eodolpassein�usionen sind im akuten Stadium der oralen �herapie wegen der sicheren Biover��gbarkeit vorzuziehen. Mit [3,4,5,6]. Eine �nalgesieverl�ngerung durch �drenalin ist o��en� �ngerung durch �drenalin ist o��en� ngerung durch �drenalin ist o��en� sichtlich nur bei kleinen Kindern gegeben [�].…”
Section: Therapie Des Akuten Schmerzes Bei Kreuzschmerzenunclassified